Formulation of unavailable diagnostic haptens for the detection of contact allergy to topical medications in the Polish Baseline Series - Radosław Śpiewak; Aldona Maciejewska; Krzysztof Niwiński (Alergologia Polska)
The necessity of routine patch testing to topical medications reflects the frequency of contact allergy to these haptens as well as their presence in many popular medicinal products. At present, Polish Baseline Series includes 7 drugs tested individually (neomycin sulfate, gentamycin sulfate, budesonide, tixocortol 21-pivalate) or in the Caine Mix III (benzocaine, dibucaine, tetracaine). After 2021, the distribution of patch test preparations of drugs as halted in Poland due to the ongoing and still unsolved debate about the legal status of patch test haptens. Nevertheless, legal obstacles did not change the epidemiological situation and patch testing with drugs is still a part of good allergy and dermatology practice. Therefore, the doctors should supplement the presently available Polish Standard I (including most frequent sensitizers except drug haptens) with drugs available from pharmacy. Ready-made medicinal products are not an optimal replacement due to relevant differences in concentrations as well as the mode of application when comparing with the diagnostic use. Moreover, excipients added to such preparations might hamper the diagnostic purpose due to their own sensitizing potential. A definitely better solution is ordering of tailor-made pharmaceutical preparations of drug haptens at concentrations optimal for patch testing. In the present article, we propose prescriptions for hapten preparations to replace the currently unavailable drugs from the Polish Baseline Series. They can be either identical with the commercial patch test preparations (neomycin sulfate, gentamycin sulfate, budesonide) or a replacement with a modified, possibly improved, composition (caine mixes). The hapten most difficult to replace is tixocortol 21-pivalate that is not available in Poland in any form. An accessible, yet not equivalent, replacement for this hapten in the baseline series might be hydrocortisone 17-butyrate in alcohol.